Polycystic Ovary Syndrome and Primary Headaches: A Narrative Review Study - Marzieh Saei Gharenaz; Mahbanoo Farhadi Azar; Fahimeh Ramezani Tehrani (Mashhad University of Medical Sciences, 2022)
Introduction: Polycystic ovary syndrome and primary headaches are common health problems in women around the world. Some evidence indicates that these two disorders may share some risk factors. This narrative review study was performed aimed to investigate the common pathways involved in the simultaneous occurrence of these two disorders. Methods: In this narrative review study, the relevant keywords such as polycystic ovary syndrome and primary headache (migraine, cluster headache and tension headache) were searched in databases of PubMed, Scopus, Web of Science, and Google Scholar with English language limitation and no time limit until Nov 2019. Inclusion criteria were observational, experimental, and review studies, and the articles which presented findings appropriate to the objectives of this review study. Findings of this study were presented qualitatively. Results: In this study, 60 extracted articles were assessed. Polycystic ovary syndrome and primary headaches like migraine have some common risk factors and clinical consequences, but the possible overlap between these two disorders has not yet been identified. Numerous evidences have suggested that lifestyle and psychological factors are important factors that contribute in the development and progression of both disorders. In addition, other possible common pathological pathways include hormonal disorders (sex hormones, thyroid hormone, and prolactin), risk factors for metabolic abnormalities (insulin resistance, hypertension, and lipid disorder), obesity, and inflammatory factors. Conclusion: The available evidence mainly indicates common pathways including hormonal, metabolic, and inflammatory abnormality in the development of polycystic ovary syndrome and primary headaches including migraine.